Factors influencing postpartum depression among Japanese parents: A prospective longitudinal study - Yuko Yamakawa; Michio Maruta; Yuya Higuchi; Akiko Tokunaga; Ryoichiro Iwanaga; Sumihisa Honda; Akira Imamura; Goro Tanaka (Wiley, 2023)
Abstract Aim Postpartum depression (PPD) may have negative effects on the parents and lead to impaired cognitive, socioemotional, and behavioral development in their children. The purpose of this study was to examine factors associated with PPD in parents during the first year after delivery. Methods This study used a self‐administered questionnaire. Questionnaires were mailed at 5 days, 3 months, 6 months, and 1 year after delivery, respectively. The particpants were 107 pairs of mothers and fathers. PPD was assessed using the Edinburgh Postnatal Depression Scale (EPDS). Data on sense of coherence (SOC), Quality Marriage Index, Social Support Scale, Mother‐to‐Infant Bonding Scale, and sociodemographic variables were collected. Multiple regression analysis was performed to examine the strength of the association between several variables and the EPDS at each survey period for fathers and mothers, respectively. Results The prevalence of PPD in the first‐year postpartum ranged from 12.1%-23.4% to 7.5%-8.4% for fathers and mothers, respectively. SOC had the strongest impact on EPDS scores for both fathers and mothers at all four survey periods. Conclusions Our findings suggest that stress coping skills are an important factor affecting PPD throughout the first‐year postpartum for both fathers and mothers.